ANALISIS PENGARUH NON PERFORMING LOAN (NPL) TERHADAP KINERJA BANK SWASTA DI INDONESIA - Achmarul Fajar; Dian Lestari; Nurinda Aulia; Alfin Naila (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
The banking industry has experienced ups and downs for decades. Declining economic activity, inflation and interest rate changes cause banks to selectively shift non performing loan surge (NPL). High NPL is an indicator of failure of the bank in managing the business. In this study aims to analyze the performance of banking NPLs in Indonesia as well as influencing factors (LDR, LAR, Inflation, BI rate, Credits given). In this study, NPL as dependent variable and LDR, LAR, inflation, BI_rate, and credit are given as independent variables. In this study, the classical assumptions are tested heterokedastisitas, multikolinearitas, and autocorrelation to determine the relationship between variables. The results concluded that the performance of banking NPLs in Indonesia in 2012 to 2016 is still well below 5%. But in the year 2016, the performance of NPL Bank Permata bad that is equal to 6.56%. Overall, in 2016 NPLs of banks almost increased except Bank BRI. The effect of the bebas variables on the NPL is sequentially given credit, inflation, LDR, LAR and BI rate. The classical test results also concluded that NPLs with LDR, LAR, inflation, BI rate, and credit provided have a strong correlation.